Treatment cost of metastatic colon cancer in Turkey - Kockaya, Guvenc; Polat, Mine; Wertheimer, Albert; Ozet, Ahmet; Malhan, Simten; Vural, İsmail Mert and Akbulat, Akif and Artıran, Guven and Gursoz, Hakkı and Kerman, Saim (Farmeconomia. Health Economics and Therapeutic Pathways, 2013)
OBJECTIVES: Colon cancer is the third most common in the top cancer incidence list in Europe. In Europe 212,000 patients die every year due to colon cancer. In Turkey 120,000-130,000 new cancer patients are diagnosed every year, 7.1% of whom are diagnosed to have developed colon cancer. Metastases will occur in up to 50% of the patients who are newly diagnosed. Survival appears to be further prolonged to more than 20 months with new pharmaceuticals; however, these new pharmaceuticals increase the total cost of care. The aim of this study is to estimate the cost implications of new colon cancer treatment options for Turkey. METHODS: Gazi University Hospital treatment protocols for colon cancer treatment were used. Cost of FUFA (5 FU/LV), FOLFIRI, FOLFOX, bevacizumab/FUFA, bevacizumab/FOLFIRI, bevacizumab/FOLFOX, irinotecan and irinotecan/cetixumab protocols were calculated. The cost of combination of protocols were calculated depending on a Markov analysis. The exchange rate was US 1 for TL 1.5. RESULTS: Depending on the life expectancy the lowest total cost was established by FUVA (US 5,359). It was followed by FOLFIRI then FOLFOX and FOLFOX, US 14,144 and US 16,553, respectively. The lowest cost for each week of life expectancy was established by FUVA with US 98. CONCLUSIONS: Only FUFA, FOLFIRI followed by FOLFIX, FOLFIRI/bevacizumab then FOLFOX then cetuximab, FOLFOX/bevacizumab then irinotecan then cetuximab/irinotecan and FOLFIRI/bevacizumab then FOLFOX then cetuximab/irinotecan were under the cost effectiveness curve. In addition no treatments ICER was under the WHO`s threshold for Turkey, except FOLFIRI then FOLFOX compared with FUVA.